Role Community Study For Increase Teacher Professionalism At State Kindergarten 2 Kongbeng East Kutai - Srywahyuni, Srywahyuni; Hermanto, Hermanto; Pujaningsih, Pujaningsih (UMSU, 2025)
This study aims to identify the implementation, benefits, and inhibiting factors of learning community activities at TK Negeri 2 Kombeng. This type of research is a qualitative field study. Data collection techniques include observation, interviews, and documentation, which were then analyzed through several stages, namely data collection, data reduction, data presentation, and conclusion drawing. The results of the study show that the establishment of a learning community serves as a relevant and effective strategy to promote collaboration among educational stakeholders such as teachers, principals, parents, and the surrounding community. The learning community functions as a forum where members actively share knowledge, experiences, ideas, and solutions to problems encountered in the learning process and school management. At TK Negeri 2 Kombeng, the formation of the learning community is based on the need to create a sustainable learning culture and to support the improvement of the quality of educational services.